Construction and preliminary validation of an instrument for understanding fighting teaching in school physical education - Pereira, Marcos Paulo Vaz De Campos; Mota, Íris Dantas da; Lacerda, Elias Barboza; Farias, Gelcemar Oliveira (Revista de Artes Marciales Asiáticas, 2020)
The purpose of this study was to construct and conduct a preliminary validation of the questionnaire on fighting and games teaching (QELJ), thus contributing to understand how fighting in school physical education is being taught. The dimensions of the instrument were created on the basis of the literature in fighting and games. The content validation process was performed by five expert judges in the field. Aiken’s V was used to quantify concordance between experts. In addition, the QELJ was tested with 17 physical education teacher in two moments, with an interval of 14 days between them. NVivo 9.2 software was used for content analyses on participants’ answers. The results showed high positive agreement rates among the evaluators, all above 0.80. The pilot study also presented good reliability results in the analysis of participants' responses in the two moments (97% for closed questions, 82% for open questions). It can be concluded that the QELJ proved to be a valid and useful tool to improve the understanding of the teaching of fighting in school physical education, although other psychometric evaluations of the instrument should be carried out in the future.